MARKETING MARGIN ACCOUNT BETWEEN THE PRODUCER AND CONSUMER PRICE OF SOME VEGETABLE CROPS IN THE PROVINCE OF BAGHDAD AND THE PRICE OF THE AGRICULTURAL SEASON FOR SUMMER 2014 - & et al., Al- Fraji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research aims to, analyze and estimate marketing margins and the relative importance of some vegetable crops in the province of Baghdad and then estimate the product share and wholesaler and retailer of consumer Iraqi dinars spent boil vegetable crops studied Results of the study showed that the margin catalog crops fresh vegetables varies from time to harvest as it was about 316 dinars Tomato and 315 for the option of water and 421.3 dinars eggplant and 448.5 dinars potato and 425.5 dinars onions dry. How much the product share of consumer spending was about %58.3 and tomatoes %59.7 of the option and water %52.3 of the eggplant and %56.2 and potatoes 49.8% of dry onions. The share of the wholesale of consumer spending about 12% and tomatoes %13.5 of the option and water %11.2 of the eggplant and %9.5 and potato %9.2 onion dry. What share of the retailer of consumer spending about % 29.7 and tomatoes 23.3% of the option and water (36.4%) of the eggplant and 34.2% and potatoes 41.0% of dry onions. The relative importance of the terms of marketing margin for vegetable crops school came first prize profit retailer as it drew %42.6, and came in second place transportation as the percentage %18.8. And the third place came the profits of the wholesaler as the percentage %17.7, And it was ranked fourth marketing operations costs as the percentage %10.1 it ranked fifth packing costs amounting to % 9.2 . It came sixth rank as loading costs amounted to %1.3. And that the margin between the search marketing is relatively high despite the decline in its absolute value, to the short distance between the producer and the consumer on the one hand and the lack of marketing tasks on the other hand care. Find recommendations came out of perhaps the most important work to raise marketing efficiency by changing market performance so that leads to lower costs functionality without modifying or reducing benefits or increasing the marketing benefits of marketing services without increasing marketing costs or achieve both.